HUMAN DIGNITY AS A COMMON ELEMENT IN INTERNATIONAL BIOLAW AND THE RIGHT TO WATER - Tzatzaki, Vicky (IUS ET SCIENTIA, 2017)
Human dignity has been a core notion in many regimes of international law, such as human rights and international humanitarian law. Respect for human dignity derives from the fundamental right to life. The right to life, considered as a peremptory rule of international law, provides human dignity with a more sophisticated status in legal terms. In other words, human dignity is no more a term with moral and ethical connotations but stemming from the right to life, it attains a legal and political dimension, evolving into a principle to be respected and protected. The present paper is divided in two parts: the first part examines human dignity in international biolaw and in the second it is traced in the right to water. Specifically, it is argued that in the regime of international biolaw, human dignity constitutes a core concept and it comes into focus primarily as an integral qualitative element; in the right to water, the international community has recognized that respect, protect and fulfill the individuals’ right to water equals to respect for human dignity. Human dignity is reaffirmed in the UNESCO Universal Declaration on Bioethics and Human Rights, being a core element of any bioethical debate, as well as in General Comment No. 15, according to which adequacy, availability, accessibility and quality of water include human dignity as a sine qua non component. However, since respect for human dignity is not yet a principle or obligation but a mere appeal for the establishment of concrete regulatory frameworks for biolaw and the right to water, it should be combined with the erga omnes obligation for the protection of the right to life, in order to solve practical and theoretical dilemmas on a global and national level.